Cyclic tests on beam-column joints of SCOPE system with different key slot lengths and corrosion levels. (15th December 2019) - Yang, Jun; Guo, Tong; Chai, Shun; Li, Aiqun
Highlights: Cyclic tests of ten corroded beam-column joints of SCOPE system were conducted. Corrosion of steel bars significantly affected seismic behaviors of the structure. Key slot length affects the seismic performance and should be carefully determined. Abstract: A frame Structure Comprised of Precast Prestressed Concrete Components (SCOPE) has been widely used in China. According to previous research, the length of non-contact lapped splice between U-shape bars and the steel strands plays an important role in seismic performance of the beam column joint. However, the splice may deteriorate due to corrosion when the frame is used in coastal region. This paper presents an experimental investigation on seismic behaviors of the corroded beam-column joints of the SCOPE system. Ten specimens with different key slot lengths and different corrosion levels were tested under cyclic loading, and their hysteretic loops, envelop curves, bearing capacity, and energy dissipation were compared and analyzed. It is observed that the corrosion of steel bars would significantly affect seismic behaviors of the structure, and most specimens showed flexural failure, while for the seriously corroded specimens with long key slots, failure might occur at the interface between the precast beam and the key slot due to severe corrosion and bond failure of the lapped splice. In general, the energy dissipation of specimens with shorter slot length was greater than that of specimens with the longer key slot under the same corrosion level. However, as the corrosion level increases, the difference became smaller.